PERENCANAAN, STRATEGI, DAN PENILAIAN DALAM DESAIN PEMBELAJARAN IPAS OLEH GURU DI SEKOLAH DASAR - Elisya Risma Salsabilla; Adzra Aunatulah Salsabila; Aa Rega Raffid Ciptandri; Muhammad Imaduddin; Arif Mahya Fanny (STKIP Subang, 2026)
The implementation of the Independent Curriculum requires teachers to design student-centered learning through integrated planning, strategies, and assessment. Natural and Social Sciences (IPAS) play an important role in developing students' critical thinking, problem-solving, collaboration, and contextual understanding of natural and social phenomena. However, several challenges still exist in practice, such as the limited availability of teaching tools, differences in student characteristics, and the complexity of implementing assessments in accordance with the principles of the Independent Curriculum. This study aims to analyze the planning, strategies, and assessment in designing IPAS learning implemented by teachers at Gulun 3 Elementary School. This study uses a descriptive qualitative approach with data collection techniques including interviews, observation, and documentation. The results show that teachers develop learning modules based on Learning Outcomes (LI) and Learning Objectives Flow (ATP) of the Independent Curriculum. The learning strategies implemented are student-centered through the use of Problem-Based Learning (PBL) and Project-Based Learning (PJBL) models, group discussions, and the use of digital media. Assessment is carried out comprehensively through diagnostic, formative, and summative assessments, which cover cognitive, affective, and psychomotor aspects. However, challenges remain, including limited technological resources and differentiated learning management. Therefore, it is necessary to improve teacher skills and strengthen teaching resources to optimize the implementation of science and knowledge learning models in elementary schools.